2002
DOI: 10.4049/jimmunol.169.7.3507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Glycoprotein 96 (B2), a Stress Protein, Functions as a Th2-Specific Costimulatory Molecule

Abstract: After the engagement of Ag receptor, most of the Th cells for their optimal activation require a second (costimulatory) signal provided by the APCs. We demonstrate the isolation and characterization of a 99- to 105-kDa protein (B2), from LPS-activated B cell surface, and its function as a Th2-specific costimulatory molecule. Appearance of B2 as a single entity on two-dimensional gel electrophoresis and as a distinct peak in reverse-phase HPLC ascertains the fact that B2 is homogeneous in preparation. Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…These findings, to some extent at least, confirm a previous study that reported gp96 acts as a Th2-specific costimulatory molecule (Banerjee et al 2002). The receptors and signaling events underlying these effects are currently under investigation, as are the in vivo immunoregulatory consequences of high-dose gp96 administration.…”
Section: Figsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings, to some extent at least, confirm a previous study that reported gp96 acts as a Th2-specific costimulatory molecule (Banerjee et al 2002). The receptors and signaling events underlying these effects are currently under investigation, as are the in vivo immunoregulatory consequences of high-dose gp96 administration.…”
Section: Figsupporting
confidence: 77%
“…In this regard, a number of investigators have reported that gp96 induces the maturation of, and cytokine secretion from, these and other APCs and increases their capacity to stimulate the proliferation of T cells (Basu et al 2000;Singh-Jasuja et al 2000a;Zheng et al 2001;Baker-LePain et al 2002;Reed et al 2003). Gp96 might also have direct effects on T cells because a protein expressed on the surface of lipopolysaccharide (LPS)-activated B cells (B2), which has been identified as gp96, has been reported to act as a T-helper 2 (Th2)-specific costimulatory molecule for murine splenic T cells (Banerjee et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In independent studies, Habich et al (15) reported that ␣ 2 M competes with gp96 for binding macrophage, as does gp96 itself. Banerjee et al (16) showed that Th cells express CD91 on the cell surface and that gp96 binds CD91 on the T helper (Th) cell surface. Such binding is abrogated by anti-CD91 Abs but not control Abs.…”
mentioning
confidence: 99%
“…The possibility that HSP96 or other members of the HSP family may directly interact with lymphocytes is also supported by recent data reporting the binding of HSP96 and HSP70 to murine CD4 + T lymphocytes (37) or human NK cells (38) 5 However, other receptors, such as CD94, TLR2, and TLR4, which have been found to mediate HSP70 binding to NK cells (38,40) or to be up-regulated in CD56 + NK and T cells on virus or parasite infection (41,42), could also play a role in this phenomenon.…”
Section: Discussionmentioning
confidence: 51%